Albiglutide does not impair the counter‐regulatory hormone response to hypoglycaemia: a randomized, double‐blind, placebo‐controlled, stepped glucose clamp study in subjects with type 2 diabetes mellitus1. Issue 1 (26th October 2014) - Hompesch, M.; Jones‐Leone, A.; Carr, M. C.; Matthews, J.; Zhi, H.; Young, M.; Morrow, L.; Reinhardt, R. R.
<x xml:space="preserve">Abstract</x> Aim To determine if the glucagon‐like peptide‐1 (GLP‐1) receptor agonist albiglutide, once weekly, impairs counter‐regulatory responses during hypoglycaemia. Methods We conducted a randomized, double‐blind, parallel, placebo‐controlled study in subjects with type 2 diabetes mellitus. A single dose of albiglutide 50 mg (n = 22) or placebo (n = 22) was administered on day 1. Glucose was clamped on day 4 (to coincide with the approximate albiglutide maximum plasma concentration) at 9.0, 5.0, 4.0, 3.3 and 2.8 mmol/l (162, 90, 72, 59.4 and 50.4 mg/dl), with a post‐clamp recovery period to 3.9 mmol/l (70 mg/dl). Hormone measurements were made at each plateau and adverse events (AEs) were recorded. Results The counter‐regulatory hormones glucagon, epinephrine, norepinephrine, growth hormone and cortisol were appropriately suppressed when plasma glucose levels were >4.0 mmol/l (>72 mg/dl), but increased in the albiglutide and placebo groups with glucose levels <3.3 mmol/l (<59.4 mg/dl) in response to hypoglycaemia. The area under the curve geometric mean ratios (albiglutide : placebo), calculated from the clamped plateau of 4.0 mmol/l (72 mg/dl) to the glucose recovery point, were not significantly different for any of the counter‐regulatory hormones. When plasma glucose levels were >5.0 mmol/l (>90 mg/dl), albiglutide increased pancreatic β‐cell secretion of C‐peptide in a glucose‐dependent manner to a greater extent than did placebo, and it was suppressed in each group when levels were <4.0 mmol/l (<72 mg/dl). No significant difference between groups was observed in the recovery time to glucose level ≥3.9 mmol/l (≥70 mg/dl). There were no clinically relevant differences in AEs or other safety variables. Conclusions A single 50‐mg dose of albiglutide was well tolerated and did not impair the counter‐regulatory response to hypoglycaemia. These data provide mechanistic evidence supporting the low intrinsic hypoglycaemic potential of albiglutide.